Chasing the Milky Way - Moulton, Erin E. (Philomel Books, an imprint of Penguin Group (USA), 2014)
Lucy Peevey, twelve, and her best friend Cam are perfecting the robot that could win a competition, a scholarship, and a way out of Sunnyside Trailer Park when Lucy's mother goes off her medication and her manic-depressive disorder goes out of control.